[Claiming our future ; Coup rumors ; North Andrews [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1990)
Looks into the conflict between the townfolk and the logging company on the issue of the environment in Gabaldon, Nueva Ecija. Rumors of a coup continue to fly thick and fast inspite official denials. Interviews with an unconventional disc jockey.
Claiming our future (19 min.) -- Coup rumors (17 min.) -- North Andrews (12 min.)
VHS.
Keywords: De Castro, Andrew; Logging -- Philippines -- Gabaldon (Nueva Ecija).; Coups d'etat -- Philippines; Disc jockeys -- Philippines; Floods -- Philippines -- Gabaldon (Nueva Ecija); Rumor -- Philippines -- Manila Metropolitan area